Jonathan Edwards and the gospel of love - Story, Ronald (University of Massachusetts Press, 2012)
"Jonathan Edwards has long epitomized the Puritan preacher as fiery scold, fixated on the inner struggle of the soul and the eternal flames of hell. In this book, Ronald Story offers a fundamentally different view of Edwards, revealing a profoundly social minister who preached a gospel of charity and community bound by love. The first chapters trace Edwards's life and impact, examine his reputation as an intellectual, Calvinist, and revivalist, and highlight the importance for him of the gentler, more compassionate concepts of light, harmony, beauty, and sweetness. Story then explains what Edwards means by the "Gospel of Love"--Individual than interpersonal, and whose central feature is the practice of charity to the poor and the quest for loving community in this world, the chief signs of true salvation. As Edwards preached in his sermon "Heaven Is a World of Love," the afterlife itself is social in nature because love is social. Drawing on Edwards's own sermons and notebooks, Story reveals the minister's belief that divine love expressed in the human family should take us beyond tribalism, sectarianism, provincialism, and nationality. Edwards offers hope, in the manner of Walter Rauschenbusch, Karl Barth, Martin Luther King Jr., and other great "improvers," for the coming of a world without want and war. Gracefully and compellingly written, this book represents a new departure in Edwards studies, revising the long-standing yet misleading stereotype of a man whose lessons of charity, community, and love we need now more than ever."--Project Muse